PERAN KEPEMIMPINAN KEPALA SEKOLAH DALAM UPAYA MENGEMBANGKA PROFESIONALISME GURU - Sri Indriani; Enung Hasanah (JURNAL KEPEMIMPINAN DAN PENGURUSAN SEKOLAH, 2021)
The principal is a strategic element strengthening the professional quality of reachers ini improve the quality of education in an institution that has a direct impact on learning. However, this is not supported by professional teachers, and teacher are still have standards that have been set even more so those in eastem areas that still have lack of professional education personnel with a very low number of teaching staff as well as the mismatch of the available aducation personnel with the subjects is still lacking. Therefore, the aim of this research is to examine the leadership roles of the principal in the effort develop teacher professionalism. This method uses literature review or litearture research, which is to study literature books that are in accordance with the teory discussed in the scope principal leadership and also analyzes scientific articles cited with using spinger link and google scholar. The results is showed that the role of leadership the principal by providing guidance, motivation and supervisioan, they are can improve professionalism of teachers in work which can have implication for learing process. Leadership principals in an effort to develop teachers professionalism can be done through, such as : 1) teacher attend training and seminars, 2) join to workshops or activities like KKG/MGMP/MGBK are used in designing or developing a learing curriculum and learing media.